2015
DOI: 10.1007/s11657-015-0219-2
|View full text |Cite
|
Sign up to set email alerts
|

Association and relative importance of multiple obesity measures with bone mineral density: the National Health and Nutrition Examination Survey 2005–2006

Abstract: All obesity measures were positively associated with femoral neck BMD, but not with lumbar spine BMD. Hip circumference was the most important obesity measure in relation to BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 38 publications
2
31
0
1
Order By: Relevance
“…The increase in fracture risk in T2DM is indeed observed in the setting of normal BMD. Possible explanations for such a "paradox of BMD" are the high frequency of obesity in these patients, and the well-known positive association between high BMI and high BMD (23). Additionally, the role of insulin resistance, and consequent high insulin levels, has been postulated, even though some studies failed to find a positive association with BMD independently of BMI (24).…”
Section: Advanced Glycation End-productsmentioning
confidence: 99%
“…The increase in fracture risk in T2DM is indeed observed in the setting of normal BMD. Possible explanations for such a "paradox of BMD" are the high frequency of obesity in these patients, and the well-known positive association between high BMI and high BMD (23). Additionally, the role of insulin resistance, and consequent high insulin levels, has been postulated, even though some studies failed to find a positive association with BMD independently of BMI (24).…”
Section: Advanced Glycation End-productsmentioning
confidence: 99%
“…Although obesity was thought to be protective against all fractures, it substantially increased the risk of fractures in the ankle or lower leg Compston et al [2014] 52,939 women Inverse linear associations between BMI or weight and hip, spine, and wrist fracture Ho-Pham et al [2014] Meta-analysis: 44 studies, 20,226 individuals (4966 men and 15,260 women), 18-92 years old Lean mass exerts a greater effect on BMD than fat mass in men and women Søgaard et al [2015] 19,918 postmenopausal women; 23,061 men Abdominal obesity (CV) was associated with an increased risk of hip fracture Copês et al [2015] 1057 women Prevalence of fractures in obese and nonobese women was similar (17.3% versus 16.0%); 41.4% of all fractures occurred in obese women Yang and Shen [2015] 5287 individuals, 8-69 years old All obesity measures were positively associated with femoral neck BMD, but not with lumbar spine BMD. Greater BMI and hip circumference were the most important obesity measure in relation to BMD BMI, body mass index; CI, confidence interval; CV, cardiovascular; HBMD, high bone mineral density; LBMD, low bone mineral density; NS, nonsignificant; RR, relative risk; aFM, abdominal fat mass.…”
Section: Studymentioning
confidence: 99%
“…In this study, diabetic and non-diabetic groups were matched according to age, sex and body mass index (BMI). Type 2 diabetes is routinely associated with overweight [30,31] and higher BMI is positively associated with BMD [32]. Nevertheless, overweight may be less protective against fractures than previously estimated [33,34] and recently it has been demonstrated that higher BMI did not modify BMD loss [2].…”
Section: Discussionmentioning
confidence: 98%